The Impact of E-Commerce Strategies on Firm Value: Lessons from Amazon.com - Darren Filson; Karyn Williams (Claremont McKenna College, Department of Economics, 2001)
Managers would like to understand which strategies generate value in e-commerce environments, and researchers are just beginning to explore this issue. Which strategies are useful and which are not? In a step towards answering this question, we estimate the impacts of several competitive strategies on the value of Amazon.com, the well-known Internet retailer, during its first 1000 days as a publicly traded firm. The strategies analyzed include pricing, offline expansion, alliance formation, product line expansion, and service improvement. The results provide insight into the usefulness of various ways of competing online and could be useful for strategic planning in new Internet ventures.
Keywords: G31; D81; L21; L81; M21; 330; alliance; competitive advantage; competitive strategy; event studies; internet; valuation